1990
DOI: 10.2519/jospt.1990.11.12.605
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Muscle Function and Ankle Stability

Abstract: The purpose of this investigation was to document the degree of weakness present in the medial and lateral muscle groups of individuals with chronically unstable ankles. Peak isometric and isokinetic torque measurements were collected bilaterally during the motion of inversion-eversion from 33 subjects, ages 17 to 54, reporting unilateral chronic lateral instability. Values were then compared between the involved and uninvolved sides. A modified Romberg test was also performed bilaterally to determine gross ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
2
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 12 publications
6
101
2
6
Order By: Relevance
“…This type of condition leads to poor muscle activation, joint motion, and alteration of the center of pressure of the foot (20). Furthermore, Lentell et al (22) reported that instability of the ankle is not a result of muscle weakness but is associated with the presence of proprioceptive deficits. These kinematic outcomes result in modifications throughout the kinetic chain that alter the inverse dynamics of the knee and hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of condition leads to poor muscle activation, joint motion, and alteration of the center of pressure of the foot (20). Furthermore, Lentell et al (22) reported that instability of the ankle is not a result of muscle weakness but is associated with the presence of proprioceptive deficits. These kinematic outcomes result in modifications throughout the kinetic chain that alter the inverse dynamics of the knee and hip.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that consistent activity and training of the lower extremities may infiuence the reaction time, proprioception, and muscle activation of crural musculature (1,2,22,24,25,35). Peroneal muscle reaction time has been examined in multiple research models and disease states.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found no association between muscle weakness and ankle instability [14,37,43,44] .…”
Section: Rehabilitation For Ankle Sprainmentioning
confidence: 85%
“…Some studies have identified invertor strength deficits, 107,187,202,218,278 whereas others have not. 156,180 Evertor strength deficits have also been identified in some studies 107,202,242 but not others. 156,180,218,278 Single-Limb Balance…”
Section: Isokinetic Muscle Strength Of Inversion and Eversionmentioning
confidence: 99%